'Killing a mosquito with a hammer': Al-Shabaab violence and state security responses in Kenya. (4th May 2017) - Lind, Jeremy; Mutahi, Patrick; Oosterom, Marjoke
Abstract: Networked, transnational forms of violence pose a significant threat to peace and security in a number of sub-Saharan African countries. In recent years, Kenya has witnessed an expanding number of attacks involving Al-Shabaab – the Somali-based militant organisation. Kenya's state responses to these attacks derive from a social construction of Somalis as a threatening presence, justifying a raft of hard security measures. However, this targeting has been counter-productive by driving a deeper wedge between Somalis, other Muslims and the state, and levels of Al-Shabaab violence have remained high. Seen from the social and political margins that Kenya's Somali and Muslim populations occupy, recent violence continues a long-standing dynamic of insecurity in which the state itself is a central actor. Internal stress relating to state-led planning of social order built on unequal citizenships and the use of violence, enmesh with the external threat of Al-Shabaab, producing the conditions for insurgency and violence to spread. Reducing violence and building peace require greater understanding of how violence and security are seen and experienced at the margins.